Knowledge, interest, predisposition and evaluation of functional foods in Spanish dietitians-nutritionists and experts in human nutrition and dietetics Conocimientos, interés, predisposición y valoración sobre alimentos funcionales por parte de dietistas-nutricionistas y expertos en nutrición humana y dietética españoles - J. Basulto Marset; P. Casas-Agustench; N. Babio Sánchez; J. Salas-Salvadó (Nutrición Hospitalaria, 2012)
Introduction: Little research has been conducted into the attitudes and knowledge of dietitians-nutritionists (DN) or of experts in human nutrition and dietetics (EHND) regarding functional foods (FFs). Objectives: To evaluate the knowledge of, interest in and predisposition towards FFs in Spanish DN and EHND, and how these professionals rate the potential benefits and risks associated with consuming FFs. Methods: 2100 DN and 122 EHND were asked to participate in a self-administered questionnaire. The results were expressed using percentages and the DN responses were compared with those of the EHND by means of chi-squared test. A significant difference was regarded as having been obtained if P < 0.05. Results: 204 DN and 112 EHND responded. After eliminating 45 surveys due to anomalies, 268 surveys were analyzed (170 from the DN, 8.1% participation; 98 from the EHND, 80.3% participation). No statistically significant differences were observed between the responses of the DN and the EHND except in: 1) the view that it was "dangerous" to consume certain FFs ≥ 4 times a day; and 2) the knowledge of the population regarding in which situations certain FFs should be consumed. Most of the professionals demonstrated good knowledge of FFs, consumed FFs, showed a positive attitude towards FFs and thought that the information provided to the consumer is insufficient. Discussion and conclusions: FFs are generally accepted by nutritional professionals. However, further study is required into the discrepancies between DN and EHND regarding the view that it is "dangerous" to consume certain FFs and regarding their evaluation of whether the public know in which situations certain FFs should be consumed. Introducción: La actitud y los conocimientos de los dietistas-nutricionistas (DN) o de los expertos en nutrición humana y dietética (ENhD) en relación a los alimentos funcionales (AFs) ha sido poco investigada. Objetivos: Evaluar en DN y en ENhD españoles el conocimiento sobre AFs, el interés y la predisposición hacia ellos, así como su valoración sobre los potenciales beneficios y riesgos asociados a su consumo. Métodos: Se solicitó a 2100 DN y a 122 ENhD su participación en una encuesta autoadministrada. Se valoraron los resultados mediante porcentajes y se compararon las respuestas de DN con las de ENhD mediante el test de chicuadrado. Se consideró diferencia significativa si P < 0,05. Resultados: Respondieron 204 DN y 112 ENhD. Tras eliminar 45 encuestas por incongruencias, se analizaron 268 encuestas (170 de DN, 8,1% de participacion; 98 de ENhD, 80,3% de participacion). No se observaron diferencias estadisticamente significativas entre las respuestas de DN y ENhD excepto en: 1) la consideracion como "peligroso" el hecho de consumir ≥ 4 veces/dia determinados AFs; y 2) el conocimiento de la poblacion acerca de en que situaciones consumir determinados AFs. La mayoria de los profesionales estudiados presentan buenos conocimientos sobre AFs, los consume, muestran una actitud positiva hacia ellos, y considera que la informacion aportada al consumidor es insuficiente. Discusión y conclusiones: Los AFs son en general aceptados por los profesionales de la nutrición. Sin embargo, la discrepancia observada acerca de la consideración como "peligroso" un alto consumo de determinados AFs, y del conocimiento de la población sobre cuándo consumir determinados AFs requiere ser estudiada con mayor profundidad.